Construction of Polygons with Scratch and Computational Thinking - Stoppel, Hans-Jürgen

Explainable AI as a Rhetorical Technology: Promoting Civic Virtue in the Age of AI - Reijers, Wessel (Topoi)
Abstract Is explainable AI feasible and desirable, and are explanations of AI decisions always good? Many answer this question in the affirmative, but there is a growing discourse that is suspicious of the promises of explainable AI used to explain decisions towards users, considering it unfeasible, undesirable, and even potentially misleading. Could explainable AI be just a rhetorical foil? This paper proposes that, yes, explainable AI is a rhetorical technology but no, this does not necessarily make it undesirable. It starts by revisiting this debate according to the initial charge against rhetorics by Plato and Aristotle’s response, considering rhetoric pharmacologically, as not only a poison but also a cure for political life. It argues that, just as rhetoric was necessary to take care of the temporalities of public life, in court, the public event, and the assembly, so may explainable AI contribute to a rhetorical context. Yet, whether it does so is conditioned on the extent to which it cultivates the civic virtues relative to a respective context. The paper considers the examples of predictive policing, credit scoring, and prediction markets to argue about ideal states – civic virtues that may be cultivated in each appropriate context – and deviations that point at the risks of explainable AI to lead to domination, conformism, and political recalcitrance.

Polylogarithmic time algorithms for shortest path forests in programmable matter - Padalkin, Andreas; Scheideler, Christian (Distributed Computing)
Abstract In this paper, we study the computation of shortest paths within the geometric amoebot model , a commonly used model for programmable matter. Shortest paths are essential for various tasks and therefore have been heavily investigated in many different contexts. We consider the reconfigurable circuit extension of the model where the amoebot structure is able to interconnect amoebots by so-called circuits. These circuits permit the instantaneous transmission of simple signals between connected amoebots. We propose distributed algorithms for the shortest path forest problem where, given a set of k sources and a set of $$\ell $$ ℓ destinations, the amoebot structure has to compute a forest that connects each destination to its closest source on a shortest path. Our main results are two algorithms for hole-free structures. The first algorithm constructs a shortest path tree for a single source within $$O(\log \ell )$$ O ( log ℓ ) rounds, and the second algorithm a shortest path forest for an arbitrary number of sources within $$O(\log n \log ^2 k)$$ O ( log n log 2 k ) rounds. The former algorithm also provides an O (1) rounds solution for the single pair shortest path problem (SPSP) and an $$O(\log n)$$ O ( log n ) rounds solution for the single source shortest path problem (SSSP) since these problems are special cases of the considered problem. Then, we adapt the latter algorithm to an offset version of the problem. This allows us to solve the problem for amoebot structures with holes within $$O(h \log ^3 n)$$ O ( h log 3 n ) rounds w.h.p. where h denotes the number of holes.

Arbeitsplatz-KI: Zwölf Gestaltungsanker zur erfolgreichen Ko-Transformation von Mitarbeitenden, Prozessen & Strategie in der Finanzindustrie - Strich, Franz; Trang, Simon Thanh-Nam

Preferences for Taxing Wealth and Income - Maiterth, Ralf; Piper, Yuri; Schneider, Cornelius
We examine German individuals' preferences for income and wealth taxation and, importantly, the interplay between these two tax instruments. While prior research often examines wealth tax preferences in isolation, actual tax systems consist of multiple interacting taxes. To capture this dynamic, we elicit preferred tax burdens in a large-scale online experiment with 2,702 participants randomly assigned to one of four treatment groups: respondents state either an unspecified overall tax burden, separate income and wealth tax burdens, an income tax burden only, or a wealth tax burden only. Our baseline estimates reveal average (marginal) tax rates of approximately 17.4% (18.9%) for income and 4.1% (2.3%) for wealth. We find that participants associate wealth with an ability-to-pay taxes: when a wealth tax is not explicitly available, preferred income tax rates are approximately 30% higher. However, when both instruments are available, participants do not treat them as substitutes. Instead, they appear to treat the two taxes as separate mental bins: the standalone income and wealth tax burdens are combined in a notably additive manner, resulting in a significantly higher overall tax burden. Further, respondents apply implicit exemptions for low levels of wealth and favor a wealth tax base focused primarily on financial assets and real estate other than the primary residence.

Wie kommt der „grüne“ Strom in die Steckdose? – Eine multidimensionale Analyse der Vorstellungen von Grundschulkindern zu nachhaltiger Energienutzung - Kirsch, Alexander; Hellmich, Frank; Blumberg, Eva; Puppe, Ricardo (Vorstellungen von Kindern zu Themenfeldern der Nachhaltigkeit)

Schattenprinzip und Klimawandel - Entwicklungschancen für Lehrende und Lernende im Kontext des Ökologischen Lernens, erarbeitet am Beispiel der Massentierhaltung - Garske, Volker (Handbuch der Religionen)

Semantics-Aware Caching for Concept Learning - Kamdem Teyou, Louis Mozart; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Lecture Notes in Computer Science)

A Possible Human-Centered Embedding Space Search in Degenerate Clifford Algebras - Roberts, Isaac; Kamdem Teyou, Louis Mozart; Schulz, Alexander; Kouagou, N'Dah Jean; Ngonga Ngomo, Axel-Cyrille; Hammer, Barbara (ESANN 2026 proceedings)

X‐Ray Investigation of the Thermal Expansion Coefficient of Cubic Gallium Nitride on 3C‐SiC (001)/Si (001) Substrates - As, Donat Josef; Meier, Falco; Mahler, Pascal; Meier, Cedrik (physica status solidi (b))
This work investigates the temperature dependence of the lattice constant a exp of cubic GaN/3C‐SiC/Si (001) epilayers grown at 740°C by plasma‐assisted molecular beam epitaxy is investigated. High resolution X‐ray diffraction is performed to determine the lattice constant, using an Anton–Paar DHS1100 stage to vary the sample temperature from 25°C to 900°C, calibrated against the underlying single‐crystalline silicon substrate. A linear increase in a exp with rising temperature is observed. The thermal expansion behaviour is modelled using Debye´s phonon dispersion. The fitted lattice parameters are used to calculate the thermal expansion coefficient (TEC). At room temperature the TEC is determined to be α Debye ≈ 5.25 × 10 −6 K −1 . We further compare the TEC of the cubic GaN epilayer to that of free‐standing hexagonal GaN using the crystallographic relationship of , demonstrating good agreement between both phases. Using literature values for the elastic constants of cubic GaN, the corresponding elastic moduli and Debye temperature Θ D are calculated. An average value of Θ D of ≈905 ± 25 K is obtained, which is very close to our experimental results. Moreover, tensile strain is found to be present in our sample at room temperature, leading to an increase in the TEC. The impact of strain on the thermal properties of cubic GaN is discussed.

Numerical approaches to entangling dynamics from variational principles - Offen, Christian; Wembe, Boris; Ares, Laura; Sperling, Jan; Ober-Blöbaum, Sina (Journal of Physics A: Mathematical and Theoretical)
Abstract In this work, we address the numerical identification of entanglement in dynamical scenarios. To this end, we consider different programs based on the restriction of the evolution to the set of separable (i.e., non-entangled) states, together with the discretization of the space of variables for numerical computations. As a first approach, we apply linear splitting methods to the restricted, continuous equations of motion derived from variational principles. We utilize an exchange interaction Hamiltonian to confirm that the numerical and analytical solutions coincide in the limit of small time steps. The application to different Hamiltonians shows the wide applicability of the method to detect dynamical entanglement. To avoid the derivation of analytical solutions for complex dynamics, we consider variational, numerical integration schemes, introducing a variational discretization for Lagrangians linear in velocities. Here, we examine and compare two approaches: one in which the system is discretized before the restriction is applied, and another in which the restriction precedes the discretization. We find that the "first-discretize-then-restrict" method becomes numerically unstable, already for the example of an exchange-interaction Hamiltonian, which can be an important consideration for the numerical analysis of constrained quantum dynamics. Thereby, broadly applicable numerical tools, including their limitations, for studying entanglement over time are established for assessing the entangling power of processes that are used in quantum information theory.

Numerical approaches to entangling dynamics from variational principles - Offen, Christian; Wembe, Boris; Ares, Laura; Sperling, Jan; Ober-Blöbaum, Sina (Journal of Physics A: Mathematical and Theoretical)
Abstract In this work, we address the numerical identification of entanglement in dynamical scenarios. To this end, we consider different programs based on the restriction of the evolution to the set of separable (i.e., non-entangled) states, together with the discretization of the space of variables for numerical computations. As a first approach, we apply linear splitting methods to the restricted, continuous equations of motion derived from variational principles. We utilize an exchange interaction Hamiltonian to confirm that the numerical and analytical solutions coincide in the limit of small time steps. The application to different Hamiltonians shows the wide applicability of the method to detect dynamical entanglement. To avoid the derivation of analytical solutions for complex dynamics, we consider variational, numerical integration schemes, introducing a variational discretization for Lagrangians linear in velocities. Here, we examine and compare two approaches: one in which the system is discretized before the restriction is applied, and another in which the restriction precedes the discretization. We find that the "first-discretize-then-restrict" method becomes numerically unstable, already for the example of an exchange-interaction Hamiltonian, which can be an important consideration for the numerical analysis of constrained quantum dynamics. Thereby, broadly applicable numerical tools, including their limitations, for studying entanglement over time are established for assessing the entangling power of processes that are used in quantum information theory.

Cayley Commutator-free Methods for Krotov-Type Algorithms in Quantum Optimal Control - Wembe Moafo, Boris Edgar; Ali, Usman; Meier, Torsten; Ober-Blöbaum, Sina
This paper presents a class of structure-preserving numerical methods for quantum optimal control problems, based on commutator-free Cayley integrators. Starting from the Krotov framework, we reformulate the forward and backward propagation steps using Cayley-type schemes that preserve unitarity and symmetry at the discrete level. This approach eliminates the need for matrix exponentials and commutators, leading to significant computational savings while maintaining higher-order accuracy. We first recall the standard linear setting and then extend the formulation to nonlinear Schrödinger and Gross-Pitaevskii equations using a Cayley-polynomial interpolation strategy. Numerical experiments on state-transfer problems illustrate that the CF-Cayley method achieves the same accuracy as high-order exponential or Cayley-Magnus schemes at substantially lower cost, especially for longtime or highly oscillatory dynamics. In the nonlinear regime, the structure-preserving properties of the method ensure stability and norm conservation, making it a robust tool for large-scale quantum control simulations. The proposed framework thus bridges geometric integration and optimal control, offering an efficient and reliable alternative to existing exponential-based propagators.

Netzwerkanalysen als Bestandteil der Partizipativen Sportentwicklungsplanung - Meier, Heiko; Peper, Robert; Kukuk, Marc; Riedl, Lars (Planen. Beteiligen. Bauen. Bewegen. 16. Jahrestagung der dvs-Kommission „Sport und Raum“ vom 19.–20.09.2024 in Bad Driburg & Paderborn)

Non static exponential turnpike property for optimal control problems with symmetries and boundary conditions - Maslovskaya, Sofya; Ober-Blöbaum, Sina; Wembe Moafo, Boris Edgar
Optimal control problems with symmetries often admit a non stationary turnpike property called trim turnpike, which characterizes the convergence of optimal solutions to certain symmetry induced trajectories called trim primitives. In this paper we establish an exponential trim turnpike property for a class of optimal control problems with structural properties related to Abelian Lie group symmetries. The key ingredient of our approach is the introduction of an appropriate reduced optimal control problem. We show that extremals of the original problem can be characterized through a reduced Hamiltonian boundary value problem that coincides with the optimality system of the reduced problem. Under a hyperbolicity assumption on the equilibrium of the corresponding reduced Hamiltonian system we prove that optimal trajectories remain exponentially close, up to boundary layers near the endpoints, to a trim primitive defined by the static reduced problem. The theoretical results are illustrated on three representative examples: linear and nonlinear problems with quadratic cost and the Kepler orbital transfer problem.

Numerical approaches to entangling dynamics from variational principles - Offen, Christian; Wembe, Boris; Ares, Laura; Sperling, Jan; Ober-Blöbaum, Sina (Journal of Physics A: Mathematical and Theoretical)
In this work, we address the numerical identification of entanglement in dynamical scenarios. To this end, we consider different programs based on the restriction of the evolution to the set of separable (i.e., non-entangled) states, together with the discretization of the space of variables for numerical computations. As a first approach, we apply linear splitting methods to the restricted, continuous equations of motion derived from variational principles. We utilize an exchange interaction Hamiltonian to confirm that the numerical and analytical solutions coincide in the limit of small time steps. The application to different Hamiltonians shows the wide applicability of the method to detect dynamical entanglement. To avoid the derivation of analytical solutions for complex dynamics, we consider variational, numerical integration schemes, introducing a variational discretization for Lagrangians linear in velocities. Here, we examine and compare two approaches: one in which the system is discretized before the restriction is applied, and another in which the restriction precedes the discretization. We find that the "first-discretize-then-restrict" method becomes numerically unstable, already for the example of an exchange-interaction Hamiltonian, which can be an important consideration for the numerical analysis of constrained quantum dynamics. Thereby, broadly applicable numerical tools, including their limitations, for studying entanglement over time are established for assessing the entangling power of processes that are used in quantum information theory.

Don’t touch me there/Touch my body. Zur Vielstimmigkeit und Unstimmigkeit besungener (Be-)Rührungswünsche - Brinkmann, FRank Thomas; Jacke, Christoph (beRÜHRUNGen. Leibliches, seelisches und existentielles Geschehen in der Popkultur)

Updating at the Expense of Demand? The Case of Platform Apps - Jabr, Wael; Gutt, Dominik; Neumann, Jürgen; Kundisch, Dennis (Information Systems and e-Business Management)

Business Model Prototyping and Evaluation from an Ecosystem Perspective: An Actor-based Modeling Framework for Using System Dynamics - Ksouri-Gerwien, Christoph; Vorbohle, Christian (Information Systems and e-Business Management)

Phase Noise Metrology - Bahmanian, Meysam; Scheytt, J. Christoph; Meyne, Nora; Kleine-Ostmann, Thomas (Springer Series in Optical Sciences)
Abstract Phase noise is one of the most important properties of oscillators that limit the capacity of high-frequency communication systems. In heterodyne conversion schemes, the phase noise of the local oscillator will be multiplied and up-converted to the transmission channel. Therefore, accurate characterization of the oscillators is highly important for the design of THz communication systems. Especially when it comes to the characterization of high-quality oscillators with extremely low phase noise, traceable measurement methods are not available. In this chapter, the mathematical model and definition of the amplitude noise (AM noise) and phase noise (PM noise) are given. Different phase noise definition standards such as single sideband (SSB) and double sideband will also be provided. Phase noise measurement techniques such as frequency discrimination and phase-locked loop (PLL) technique will be discussed. The standard two-channel cross correlation for statistical analysis of phase noise at levels below the detection limit of the phase noise receiver will be explained with mathematical formalism.